The Academy - T.Z. Layton (First Touch Books for Young Readers, 2022)
While Leo longs to make the pros one day, he has no idea how to achieve this goal$1 (Buntil a professional scout pays a chance visit to one of Leo$1 (Bs games and extends an invitation to try out for the London Dragons youth squad, known as The Academy. Leo is stunned. The London Dragons isn$1 (Bt just any old soccer team. It$1 (Bs a world-famous English Premier League team. Soon Leo is off to a whole new country, embarking on the greatest adventure of his life. The downside? Only eleven players can make the team. Eleven out of two hundred of the very best youth players on the planet.s
Keywords: Sports Stories -- Sports Stories